2023
DOI: 10.3847/2041-8213/ad0bd9
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-modified Stars in Accretion Disks of Active Galactic Nuclei: The Low-luminosity Cases and an Application to Sgr A*

Jian-Min Wang,
Jun-Rong Liu,
Yan-Rong Li
et al.

Abstract: In this paper, we investigate the astrophysical processes of stellar-mass black holes (sMBHs) embedded in advection-dominated accretion flows (ADAFs) of supermassive black holes (SMBHs) in low-luminosity active galactic nuclei. The sMBH is undergoing Bondi accretion at a rate lower than the SMBH. Outflows from the sMBH-ADAF dynamically interact with their surroundings and form a cavity inside the SMBH-ADAF, thereby quenching the accretion onto the sMBH. Rejuvenation of the Bondi accretion is rapidly done by tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…) discussed in Wang et al (2023a) and point out the difference that the role of external pressure of the SMBH disk is unimportant in our model. In Section 3, we demonstrate that only a small fraction of the kinetic energy is utilized to work against the external pressure of the SMBH disk.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…) discussed in Wang et al (2023a) and point out the difference that the role of external pressure of the SMBH disk is unimportant in our model. In Section 3, we demonstrate that only a small fraction of the kinetic energy is utilized to work against the external pressure of the SMBH disk.…”
mentioning
confidence: 83%
“…As a consequence, outbursts from the BHs emerge as the Bondi explosion through the interaction between powerful outflows and dense AGN disk gas (Wang et al 2021a;Tagawa et al 2022;, resulting in thermal and nonthermal radiations (e.g., Wang et al 2021a;Tagawa et al 2023b). Wang et al (2023a) first applied the AMS model to Sgr A * with low accretion rates, naturally reproducing the orbit observed by GRAVITY/VLTI (GRAVITY Collaboration et al 2020;Gravity Collaboration et al 2023) and successfully explaining the period of the flare/ flicking in the light curve (Genzel et al 2003(Genzel et al , 2010 and spectral energy distribution (SED) from radio to X-ray bands (Witzel et al 2021;Boyce et al 2022). It is important to note that the above AMS is situated within advection-dominated accretion flows (ADAFs; .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Gravity Collaboration et al (2023) found that the Sagittarius A * flare is located at about 9 gravitational radii, consistent with the Keplerian orbital motion of the innermost accretion zone hot spot. While the physical origin of the flare remains unclear, it is proposed that a star (Leibowitz 2020) or a ∼40 M e sBH (Wang et al 2023a) orbiting periodically around the central SMBH drives this Sagittarius A * flare through interaction with the SMBH accretion disk. The star or the sBH is embedded in the advection-dominated accretion flow around the SMBH in the Galactic center.…”
Section: Introductionmentioning
confidence: 99%